Lama Menjalani Hemodialisis dan Kualitas Hidup Pasien Gagal Ginjal Kronik : Korelasi Keduanya - Ahmad Ikhlasul Amal; Erna Melastuti; Maharani Puspita Putri (Jurnal Medika Nusantara, 2026)
Hemodialysis is the primary life-sustaining therapy for patients with end-stage Chronic Kidney Disease. However, the complex burden of therapy has the potential to affect quality of life. The relationship between HD duration and quality of life still shows inconsistent results, warranting further investigation. This observational analytic study with a cross-sectional design involved 99 HD patients at Sultan Agung Islamic Hospital, Semarang. Sampling was conducted using consecutive sampling. HD duration data were collected from medical records, and quality of life was measured using the KDQOL-SF™ questionnaire. Data analysis used descriptive statistics and the Gamma correlation test. Most respondents were aged 51–70 years, female, had elementary school education, and worked as farmers. Analysis revealed a significant and positive relationship between the duration of HD and quality of life. Patients with an HD duration of more than 24 months tended to have a better quality of life compared to those with a duration of less than 12 months. The duration of hemodialysis has a strong positive correlation with the quality of life of CKD patients. This finding indicates that patient adaptation to the disease and therapy improves over time. Intensive support interventions are recommended for new patients to accelerate the adaptation process during the initial phase of therapy.